Functioning Kazakh lеxical units in the Russian speech of the residents of Kazakhstan - Nassyrova, Aliya (Przegląd Wschodnioeuropejski, 2018)
The article is devoted to the problems of bilingualism in the modern society. Bilingualism is characteristic of all the citizens of Kazakhstan. The main feature of bilingualism in our country is the quite wide application of the Russian language in all spheres of life. The changing language situation leads to the fact that a large number of Kazakh words are included into the Russian language, and assimilated by it to a varying degree. The author has analyzed the cases of the use of Kazakh lexical units in Russian texts.